(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2017)
A culture experiment was conducted to see the growth and production performance of Vietnamese koi (Anabas testudineus) with Magur (Clarias batrachus) at different stocking densities in a farmer’s ponds under semi-intensive rearing system for a period of 120 days. The experiment was conducted in three ponds at Rahmatpur of Muktagachha Upazila of Mymensingh district from 5 August to 5 December, 2013. The size of ponds were 24 (T1), 24 (T2) and 24 (T3) decimal with an average depth of 4 feet. Three different stocking densities were tested, namely treatments T1 (400 fish /decimal, 350 Vietnamese koi and 50 magur); T2 (450 fish /decimal, 400 Vietnamese koi and 50 Magur) and T3 (550 fish /decimal, 500 Vietnamese koi and 50 Magur). Ruposhi Bangla feed was used in all treatments two times daily from the beginning of the fry stocking. The initial weight of Vietnamese koi and Magur were 5±0.00 g and 2±0.00 g respectively. The initial length of Vietnamese koi and Magur were 2.54 and 3.50 cm respectively. The average highest final weight gain of Vietnamese koi was (138.71±0.03 g) observed in T1 and followed by T2 (135.65±0.12 g) and T3 (129.29±0.49 g). Similarly, the average highest final weight gain of Magur (76.00±0.58 g) was observed in T1 and followed by T2 (68.36±0.43 g) and T3 (62.61±0.58 g) respectively. The average highest final length gain of Vietnamese koi (17.38±0.05 cm) was observed in T1 and followed by T2 (17.00±0.04 cm) and T3 (16.33±0.03 cm). Similarly, the average highest final length gain of Magur (21.30±0.09 cm) was observed in T1 and followed by T2 (17.00±0.05 cm) and T3 (15.87±0.02 cm) respectively. The survival rate of the stocking Vietnamese koi and Magur were recorded 95.14 and 72.00 % in T1; 93.25 and 64.00% in T2; 90.80 and 68.00 % in T3 respectively. Fish production in T1, T2 and T3 were 48.93; 52.79 and 60.83 kg/decimal/120 days, respectively. The total production of T3 was increased with the increasing of stocking density compare to T2 and T1. The benefit-cost ratio (BCR) was higher in T3 where BCR was 1.67 and on the other two treatments BCR was 1.53 in T2 and 1.52 in T1 although the highest production was obtained in T3 but individually growth performance of Vietnamese koi and Magur were higher in T1. Based on the result of the present experiment, farmers could be suggested to rear Vietnamese koi with Magur at the stocking density of 550 fish/decimal (500 Vietnamese koi and 50 Magur) which was the highest density tried to get more production and financial benefit. Further experiment need to be conducted by taking higher density than the 550 fish/decimal for the optimization of stocking density to get more production and benefit. Asian Australas. J. Biosci. Biotechnol. 2017, 2 (3), 226-237